Determinants of Islamic Human Development Index in OIC Countries With Good Governance as Moderating Variables - Hasbi, Hasbi; Wibowo, Muhammad Ghafur (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
This study seeks to determine the effect of government spending, level of concern, and economic growth on I-HDI in the OIC countries with good governance as moderation in 2010-2019. This study uses explanatory quantitative research methods. The sampling technique in this research is non-probability sampling, with a sample of 10 countries of the Organization of Islamic Cooperation. The data analysis techniques used were descriptive analysis, Generalized Least Squares (GLS) model, hypothesis testing, and Moderated Regression Analysis (MRA) model. The results of statistical testing show that the variable government expenditure and unemployment rate do not affect the Islamic Human Development Index, while the variable economic growth has a negative effect. In addition, good governance cannot moderate the effect of government spending on the Islamic Human Development Index, while the unemployment rate and economic growth can be moderated in their influence on the Islamic Human Development Index. Thus, it can be concluded that to increase the human development index in the Islamic perspective, and there is a need for good governance so that human development in the OIC country is increasing.